2018
DOI: 10.21474/ijar01/7205
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection in Egyptian Patients With Dyspepsia: Diagnostic, Demographic, Endoscopic and Clinical Characteristics.

Abstract: Helicobacter pylori, PCR, rapid urease test, stool antigen. was revealed in 27(45%) and 10 (16.7%) had peptic ulcer disease (PUD). Conclusions: H. pylori infection rate in Egyptian patients with dyspepsia was high and gastritis was the most revealed finding upon endoscopy. No risk factors were associated with H. pylori infection among the studied adult patients. Combined rapid urease and stool antigen tests can be relied upon for detecting H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The overall feco-prevalence of H. pylori infection in this study was 51.1%. It is in line with findings from Hosaena town of southeast Ethiopia (51.4%) [ 47 ], Uganda (47.7%) [ 48 ], Bekoji (southeast Ethiopia) (47.7%) [ 13 ], Egypt (53.1%) [ 49 ], Iraq (54%) [ 50 ], and Nigeria (55%) [ 51 ]. It was lower than studies conducted in Sudan (70%) [ 26 ], Sekota (northeast Ethiopia) (64.8%) [ 52 ], and Pakistan (66.66%) [ 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…The overall feco-prevalence of H. pylori infection in this study was 51.1%. It is in line with findings from Hosaena town of southeast Ethiopia (51.4%) [ 47 ], Uganda (47.7%) [ 48 ], Bekoji (southeast Ethiopia) (47.7%) [ 13 ], Egypt (53.1%) [ 49 ], Iraq (54%) [ 50 ], and Nigeria (55%) [ 51 ]. It was lower than studies conducted in Sudan (70%) [ 26 ], Sekota (northeast Ethiopia) (64.8%) [ 52 ], and Pakistan (66.66%) [ 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…The study prevalence was also lower than that executed in urban areas of other developing countries: 81.7% in Nigeria [ 28 ], 53.0% in Egypt [ 13 ], 64.39% in Cameroon [ 15 ], and 46.2% in Nairobi [ 29 ]. However, all these studies were carried out in the hospital setting, and others used endoscopy which is a different technique from the stool antigen test used in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Many studies from Africa have shown high prevalence, for example, 81.7% in Nigeria [ 12 ], 53.0% in Egypt [ 13 ], 39.1% in Tanzania [ 14 ], 64.39% in Cameroon [ 15 ], and 73.3% (among children) and 54.8% (adults) in Kenya [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The seroprevalence value we found in the present study correlates with the results of other studies conducted in developing countries in Africa and other continents. A seroprevalence of 51.5% and 60.1% was reported in Cameroon [1,11], 62.4% in the Democratic Republic of Congo [17], 50.6% in South Africa [18], 53.0% in Egypt [19], 68% in Turkey [20], 58% in Guatemala [21], 61% in Saudi Arabia [22], 42.6% in Kuwait [23], 54.4 to 85% in South Korea [24] 83.5% in Iran [25], and 63.4% in Brazil [26] was found in these countries. The resemblances in the reported seroprevalence values and that reported in our study might be attributed to the similar socioeconomic status and life style practices among the study subjects in these countries.…”
Section: Pooled / Overall Seroprevalence Of H Pylori Infection During...mentioning
confidence: 99%